UNDERSTANDING OF OPEN UNIVERSITY PGSD S1 STUDENTS AGAINST ELECTRICAL AND MAGNETIC CIRCUITS: study of understanding electricity in elementary schools by teachers as UT students in the suburbs of Malang Regency - *, Mujadi (IJRDO - Journal of Electrical And Electronics Engineering, 2019)
The basic concept of electricity and magnetism for elementary school teachers is simply expected to be able to provide knowledge to students about electric current on a scale that is more easily understood and understood. Children at the elementary school level must be able to remember and describe the situation if in a lighting device such as a flashlight that is filled in the battery will be able to turn on the light. Flashlights and batteries are a form of closed circuit and simply can be described very easily understood and understood. Likewise an iron object that can attract similar objects from metals called magnets has a concept that is easily understood and understood by elementary school students. Lights and the attraction of objects by other objects are phenomena that need to be understood and understood by elementary school students, why and how can they occur? A trial on Open University teachers / students S1 PGSD Open University in the suburbs of Malang Regency Java Eastern Province by providing questions about electricity and magnetism which have taken the Basic Concepts of Science in Elementary School and Science Learning Materials in Elementary School through questionnaires , interviews about the concept of electric current, and magnetic force have provided very diverse answers. How far is the mastery of the concepts of electric current and magnetic force by elementary school teachers? The results obtained from this study lacked encouraging information. The percentage of achievement of mastery and understanding of the concepts of electricity and magnetism is in the percentage range between 50% to 100%. These results will have an impact on students' ability to understand the concept of science both quantitatively and qualitatively. This means that in this case students must be given the right knowledge, easy, clear, and perfect both theoretically and practically. Independent learning by teachers (students) must produce intelligent and professional independence, so that students' abilities about simple direct current and magnetic forces produce better values.